2013
DOI: 10.3732/ajb.1200574
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of phytochrome B alleviates chilling‐induced photoinhibition in rice

Abstract: Phytochrome B deficiency in rice with more stabilized chloroplast structure and higher USFA content in membrane lipids could alleviate chilling-induced photoinhibition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 62 publications
2
32
0
1
Order By: Relevance
“…The ELI was clearly decreased in the phyB mutants compared with the WT ( Figure 1C ), indicating that phyB deficiency increased membrane integrity under cold stress. This result is consistent with our previous report that a phyB mutant had a more stable chloroplast structure under cold stress (Yang et al, 2013). MDA is the degradation product of polyunsaturated lipids, and the increased membrane integrity of the phyB mutant can be partly attributed to reduced lipid peroxidation as shown by the reduced MDA content ( Figure 1D ).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The ELI was clearly decreased in the phyB mutants compared with the WT ( Figure 1C ), indicating that phyB deficiency increased membrane integrity under cold stress. This result is consistent with our previous report that a phyB mutant had a more stable chloroplast structure under cold stress (Yang et al, 2013). MDA is the degradation product of polyunsaturated lipids, and the increased membrane integrity of the phyB mutant can be partly attributed to reduced lipid peroxidation as shown by the reduced MDA content ( Figure 1D ).…”
Section: Discussionsupporting
confidence: 94%
“…MDA is the degradation product of polyunsaturated lipids, and the increased membrane integrity of the phyB mutant can be partly attributed to reduced lipid peroxidation as shown by the reduced MDA content ( Figure 1D ). However, Yang et al (2013) revealed that phyB mutants had higher unsaturated fatty acid contents in their membrane lipids, which also partly contributes to the increased membrane integrity of the phyB mutant (Yang et al, 2013). Therefore, we speculate that phyB deficiency improves membrane integrity in rice, which is an important factor for enhanced cold tolerance in phyB mutants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transgenic rice plants deficient in PhyB exhibited enhanced chilling-stress tolerance relative to the control. The phyB mutant displayed more intact chloroplasts and an increased accumulation of unsaturated fatty acids after a 24-h chilling-stress treatment, suggesting a role for PhyB in the plant's response to cold stress (Yang et al, 2013). By contrast, transgenic rice (Oryza sativa L. cv.…”
Section: Rice Plants Ectopically Expressing Phytochromementioning
confidence: 97%
“…Furthermore, down‐regulation of PHYB displayed reduced chloroplast damage, improved photosystem II efficiency and enhanced chilling tolerance in rice plants (Yang et al . ). The above reports also suggest that the down‐regulation of PHYB activates abiotic stress tolerance mechanisms.…”
Section: Photomorphogenic Phenotypes For Crop Improvementmentioning
confidence: 97%